Misinformation in decision-making: reasons, consequences & ways to overcome - Poceviciene, Rasa (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2022)
Main Goals: To show theoretically and empirically what are the main causes of misinformation in an organization; To show what are the consequences of relying on stereotypes, lack of information or overloaded information or other types of misinformation in decision-making; To find out what could be the ways to overcome it, what competences do we need for successful information management and decision-making.